Perancangan Sistem Pemantauan Kondisi Tanah - Cristin Manora; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Today, technology is experiencing rapid development after arriving in the Internet of Things (IoT) era. The Internet of Things concept is to connect physical devices to the internet so that the components connected in the system can communicate with each other. The application of the Internet of Things in agriculture is no exception, especially soil conditions for crops. IoTsoil moisture monitoring design uses an ESP8266 device, a capacitive soil moisture sensor, and Blynk. ESP8266 as a data processing component, humidity sensor to detect soil conditions, and the Blynk application to send notifications and monitor soil conditions. The results of the research on the Blynk application are effective for monitoring soil conditions in real-time.Keyword: Monitoring,Internet of Things, Blynk